A revision of the genus Olivancillaria (Mollusca: Olividae) from the southwestern Atlantic - Teso, Silvia Valeria (2011)
The genus Olivancillaria is revised and restricted to eight living species: O.deshayesiana, O. carcellesi, O. urceus, O. contortuplicata, O. orbignyi, O. teaguei, O.auricularia and O. vesica. The last two species were previously considered assubspecies. The name O. uretai is a junior synonym of O. orbignyi. The genusOlivancillaria is endemic to the Southwestern Atlantic with range from Bahia state,Brazil (~12°S) to Chubut province (42°37’S), Argentina, intertidal up to 70 m depth. Itis a clear representative of the Argentine Malacological province. Redescriptions and reillustration of types were done for each species. Shell ultrastructure, radulae, penes,siphon papillae and egg capsules are described and illustrated by SEM images. Ageometric morphometric analysis was carried out to confirm shell variation on size andshape among species. The geographic distribution of each species is provided based onfield observations as well as on museum records.